Dual Axis Solar Tracker Using Astronomic Method Based Smart Relay - Yuli Prasetyo; Budi Triyono; Hendrik Kusbandono (JAREE (Journal on Advanced Research in Electrical Engineering), 2021)
Solar energy is a renewable energy. Solar energy can be utilized using solar panels. The use of solar panels mostly uses static or silent methods. The static method on solar panels cannot produce optimal electrical energy. This is because the intensity of sunlight received by solar panels is less than optimal. So that the resulting electrical energy is not optimal. Therefore we need a system that can control solar panels automatically. this system must also be able to follow the direction of movement of sunlight. This study discusses the dual axis solar tracker using smart relay-based astronomical methods. This study adjusts the angle of the solar panels to determine the movement of the sun. This study uses a smart relay to regulate the rotation of the DC motor (Linear Actuator) and the motor power window which functions as a driving force for solar panels. Astronomical method is used for tracking sunlight. This method is based on the position of the sun according to the lunar calendar. This method uses an angle sensor in the form of a variable resistor for elevation and a rotary encoder as an azimuth angle sensor. The results obtained from this study are the optimal electrical energy output from solar energy. Keywords: renewable energy, dual axis, solar tracker, solar panel, astronomical method